Students’ Entrepreneurial Intentions by Using Theory of Planned Behavior: The Case in Indonesia - Astuti, Rifelly Dewi; Martdianty, Fanny (UI Scholars Hub, 2012)
This research aims to study the intentions of students in entrepreneurship by using the theory of planned behavior of Fishbein and Ajzein. This study was conducted in six state universities in Indonesia, namely University A in Northern Sumatra, University B in Western Sumatra, University C in Jakarta, University D in Yogyakarta, University E in Eastern Java and University F in Southern Sulawesi with total sample of 600 final year students. Data were analyzed using descriptive and inferential statistics using SPSS 11.5 and structural equation models using LISREL software to test the models. The result shows that the theory of planned behavior is proven significant to predict students’ entrepreneurial intention simultaneously in those six universities, whereas subjective norm was the strongest variable in the modeling. However, significant differences were found between results from each university, when analyzed separately. The model has different partial impact in each university, whereas the model only worked significantly in University D and F. Meanwhile, in University A, B and E some variables do not significantly influenced entrepreneurial intention and for University C, we believe that there are other variables that may explain the students’ entrepreneurial intention in University C since the model proved insignificantly to predict their entrepreneurial intention.